Consideration of the principles for stabilizing and increasing oil production at the later stage of field development (on the example of Ukraine fields) - Doroshenko, Volodymyr; Titlov, Oleksandr (Technology audit and production reserves, 2021)
The object of research is the oil industry. One of the most problematic issues in the industry is the transition of deposits to a late or final stage of their development. A significant number of deposits in Ukraine, USA, Russia, Poland, Azerbaijan began to be developed in the middle of the 19th century. To date, all the «old» fields are mostly depleted both in terms of hydrocarbon reserves and energy potential (reservoir pressure), and some are still in development, but in the so-called «late stage». At the same time, a significant number of relatively «young» fields have also entered the late stage of development, which is characterized, first of all, by a significant production of oil reserves, a progressive increase in water cut in wells, and an increase in the share of hard-to-recover reserves. As well as the transition to mechanized methods of oil production and the gradual increase in the stock of marginal wells, physical and moral deterioration of fixed assets of oil production with the threat of their mass retirement, deterioration of the ecological balance of the environment, and the like. Therefore, this work is devoted to the consideration of the principles of stabilizing and increasing oil production at a late stage of field development (using the example of Ukrainian fields). In the process of research, the original methods of classical scientific research were used, the main of which are analysis and synthesis, induction and deduction. An example of this is the proposed distribution of the structure of oil reserves into active and hard-to-recover ones. The study is based on statistical processing of a significant array of real information about the state and problems of oil production, which is typical and characteristic not only of Ukrainian fields. A wide range of directions for investment activities in the field of oil production was obtained. These are, mainly, directions for increasing the resource base, enhancing the completeness of its production, organizing a controlled and controlled displacement of oil by water, including with the use of «reverse» technology, unification of equipment for oil production, and ensuring environmental protection. Owing to the comprehensive application of these investment directions for improving the systems of field development at a later stage, it is possible to stabilize and gradually increase production, the value of which is determined by the relevant design documents.